Crystal structures of Leishmania mexicana arginase complexed with α, α‐disubstituted boronic amino‐acid inhibitors. Issue 4 (1st April 2016) - Hai, Yang; Christianson, David W.
Abstract : Crystal structures of L. mexicana arginase complexed with two α, α‐disubstituted boronic amino‐acid inhibitors were determined to resolutions of 1.28 and 1.65 Å, respectively. Abstract : Leishmania arginase is a potential drug target for the treatment of leishmaniasis because this binuclear manganese metalloenzyme initiates de novo polyamine biosynthesis by catalyzing the hydrolysis ofl ‐arginine to generatel ‐ornithine and urea. The productl ‐ornithine subsequently undergoes decarboxylation to yield putrescine, which in turn is utilized for spermidine biosynthesis. Polyamines such as spermidine are essential for the growth and survival of the parasite, so inhibition of enzymes in the polyamine‐biosynthetic pathway comprises an effective strategy for treating parasitic infections. To this end, two X‐ray crystal structures of L. mexicana arginase complexed with α, α‐disubstituted boronic amino‐acid inhibitors based on the molecular scaffold of 2‐( S )‐amino‐6‐boronohexanoic acid are now reported. Structural comparisons with human and parasitic arginase complexes reveal interesting differences in the binding modes of the additional α‐substituents, i.e. thed side chains, of these inhibitors. Subtle differences in the three‐dimensional contours of the outer active‐site rims among arginases from different species lead to different conformations of thed side chains and thus different inhibitor‐affinity trends. The structures suggest that it is possible to maintain affinity while fine‐tuning intermolecular interactions of thed side chain of α, α‐disubstituted boronic amino‐acid inhibitors in the search for isozyme‐specific and species‐specific arginase inhibitors.